Total Thyroidectomy as The Main Surgical Option for Malignant and Benign Thyroid Disease, A Prospective Study - Mohammed, Sabah A. (Journal of Neonatal Surgery, 2025)
Background and Objectives: Total thyroidectomy is regarded as the definitive management of thyroid tumors, malignant and benign. The aim of the study is to assess the safety of total thyroidectomy as the main surgical procedure for treating both malignant and benign thyroid diseases, that is to avoid technically challenging reoperation for residual diseases. Methodology: a prospective study was done for patients who have underwent thyroidectomy between December 2023 till January 2025 at a public and Privet hospital in Duhok City, Kurdistan Region, Iraq. This study represents a single surgeon experience of Thyroid diseases. A total of 102 cases were enrolled in the study. Results: The commonest complications encountered was seroma collection 9.8% followed by transient hypocalcemia 6.86% which underwent spontaneous resolution and postoperative treatment of hypocalcemia. Nerve injury, recurrent laryngeal and external branch of superior laryngeal nerves, Respiratory distress, thyroid crisis and surgical site infection had neglectable results 0.0%. The commonest presentation of the cases was mass like lesions or nodules 70.59%. Conclusion: This study supports the approach of total thyroidectomy as the main surgical technique and supports the superiority of this technique over others as it is associated with less complications and it significantly avoid the potential complications that could develop following a redo-operation for benign and malignant thyroid tumors